Risk factors for postoperative bleeding and early death in percutaneous endoscopic gastrostomy: A multicenter retrospective study. Issue 1 (13th September 2021) - Ota, Kazuhiro; Takeuchi, Toshihisa; Masuda, Daisuke; Sanomura, Makoto; Kojima, Keishi; Nakanishi, Yoshihiko; Hoshimoto, Masahiro; Higashino, Takeshi; Imoto, Akira; Okada, Toshihiko; Nouda, Sadaharu; Miyazaki, Hirota; et al.
Abstract: Background and Aim: Comprehensive reports on the risk factors for bleeding and early death after percutaneous endoscopic gastrostomy (PEG) are limited. In this multicenter study, we retrospectively investigated the risk factors for bleeding and early death after PEG. Methods: Patients ( n = 1234) who underwent PEG between 2015 and 2020 at Osaka Medical and Pharmaceutical University and its affiliated hospitals (11 institutions in total) were evaluated for postoperative bleeding and early death (within 60 days) after PEG according to patient characteristics, construction method, medical history, medications, preoperative hematological findings, and perioperative adverse events. Multivariate logistic regression was performed to identify independent predictors of bleeding and early death after PEG. Results: The risk factors for bleeding after PEG were PEG tube insertion using the modified introducer method (odds ratio [OR], 4.37; P = 0.0003), low platelet count (OR, 0.99; P = 0.014), antiplatelet therapy (OR, 2.11; P = 0.036), and heparinization (OR, 4.50; P = 0.007). Risk factors for early death were low body mass index (BMI) (OR, 0.89; P = 0.015), low serum albumin levels (OR, 0.50; P = 0.035), and comorbidity of active cancer (OR, 4.03; P < 0.0001). There was no significant association between bleeding and early death after PEG. Conclusions: We identified several risk factors for bleeding and early death after PEG. Risk factors for bleeding were PEG tube insertion using the modified introducer method, low platelet count, antiplatelet therapy, and heparinization. Risk factors for early death were low BMI, low serum albumin levels, and comorbidity of active cancer.